Beyond the search for certainty: addressing the cross-border resolution gap - Mevorach, Irit (Brooklyn Law School, 2015)
This Article compares the development of cross-border solutions for resolving and reorganizing commercial entities to those solutions available for financial institutions. This Article argues that the resolution regime for financial institutions needs to move forward from the existing international best practices approach, embodied in the Financial Stability Board (FSB) Key Attributes for Resolution Regimes, to a more formal legal framework for cross-border resolution, similar to the United Nations Commission on International Trade Law (UNCITRAL) Model Law for Cross-Border Insolvency. In doing so, this Article identifies a gap in the international infrastructure for resolutions. While UNCITRAL promulgated a model law to provide for cross-border insolvencies in 1997, there has been reluctance to take a similar path with regard to the resolution of international financial institutions, even though the stakes are very high. This Article addresses possible reasons for this reluctance, draws lessons from the commercial sphere, and explores the relevance of the UNCITRAL Model Law framework to financial institutions. This Article also analyzes the recent FSB initiative on cross-border resolution and the recently promulgated International Swaps and Derivatives Association (ISDA) Resolution Stay Protocol that seek to promote certainty in the application of resolution measures across borders. This Article argues that these primarily contract-based initiatives are important contributions to the standardization and improvement of the standards on the treatment of financial contracts in insolvency and resolution. However, the initiatives are still incomplete. Addressing the cross-border gap requires the recognition of goals beyond certainty, in the design of a cross-border framework for financial institutions.